Modern psychological risks in Ukrainian society - Moroz, Oleksandr (Національний технічний університет "Харківський політехнічний інститут", 2025)
Addiction happens when natural biological needs are prioritized to the point of destructiveness. In the context of Maslow’s Hierarchy of Needs [1], gambling addiction may arise from the fundamental need for safety, particularly financial security, when individuals seek to resolve uncertainty through risky behavior. In Ukraine gambling addiction has emerged as a significant psychological and societal issue, particularly following the legalization of gambling in 2020. This article examines the prevalence of gambling addiction, its psychological implications, and the current measures in place to address this growing concern. Drawing upon recent studies and policy developments, we explore the necessity of integrating gambling addiction assessments into employment health screenings to mitigate its impact on the workforce.
Сучасні психологічні ризики в українському суспільстві
Keywords: gambling addiction; depression; gambling; health screenings